Development of Visual Comics Physics Media on Atomic Physics Materials for Physics Learning in Senior High School - Putri Indah Ramadhani; Arita Fajar Damasari; Nova Romadhon; Trias Rizqi Febrianti; Bambang Supriadi; Lailatul Nuraini (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2022)
Physics is one of the subjects in high school which consists of facts, concepts, principles, laws, postulates, and scientific theories and methodologies. Students consider physics to be difficult because many physics concepts are abstract and difficult to understand. In this case, learning media is needed that can be used to assist teachers in clarifying the material. The purpose of this research is to develop comic visual learning media on atomic physics material. The method used in this research is research and development. Data were obtained from validation assessments by 2 material experts and 2 media experts as well as small group trials with a sample of 10 students. This research was conducted in 2022 at SMA Negeri Klakah. The result of the research is that the visual media of physics comics in terms of the material aspect has an average validity of 3.8 with a very high feasibility category. Judging from the media aspect, the physical comic visual media has an average validity of 3.6 with a very high eligibility category. The results of the trial limited to a small group obtained an average of 3.35 in the practical category. The research concludes that based on the categories of validity and practicality, the visual media of physics comics on atomic physics material that has been developed is very feasible and practical to use in learning Atomic Physics in Class XII Senior High School.